2006
DOI: 10.1071/wf05008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat and smoke treatments on the germination of six leguminous shrubby species

Abstract: The effect of high temperatures and smoke on germination was tested on the shrubland Leguminosae species, Adenocarpus lainzii, Cytisus scoparius, Cytisus striatus, Genista berberidea, Genista triacanthos, and Pterospartum tridentatum, which are abundant and widely distributed throughout the north-western Iberian Peninsula. Light thermal shocks (80°C, 5 min and 80°C, 10 min) and medium thermal shocks (110°C, 5 min and 110°C, 10 min) stimulated seed germination in C. striatus, A. lainzii, and P. tridentatum. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 30 publications
10
36
1
8
Order By: Relevance
“…P. tridentatum and U. gallii), as also observed after an experimental fire in this area (Fernández & Vega, 2014) and supports previous research that demonstrated the high resprouting capacity of those species after perturbations (Reyes et al, 2009;Muñoz et al, 2012b) along with a possible increase in heat-stimulated seed germination (Rivas et al, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…P. tridentatum and U. gallii), as also observed after an experimental fire in this area (Fernández & Vega, 2014) and supports previous research that demonstrated the high resprouting capacity of those species after perturbations (Reyes et al, 2009;Muñoz et al, 2012b) along with a possible increase in heat-stimulated seed germination (Rivas et al, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…Despite this importance for the Atlantic shrubland communities of the North-western Iberian Peninsula, not enough studies on the germinative behaviour of the dominant species and their resprouting exist (Pereiras et al 1987;Moure et al 2001;Quintana et al 2004;Rivas et al 2006). During the first post-disturbance year, the most relevant changes are due to resprouting and germination.…”
Section: Introductionmentioning
confidence: 96%
“…This indicates that the lethal threshold for germination is not passed. Negative effects of heat shock on germination have been demonstrated, in particular when seeds are exposed to temperatures above 100°C (Rivas et al 2006;Torres et al 2006;Vivar-Evans et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Several plant species from Mediterranean regions are therefore known to have their seed dormancy broken by heat shock (Herranz et al 1998;Hanley et al 2001;Rivas et al 2006;Luna et al 2007), a phenomenon also encountered for species occurring in Australian heathland, grassland or forest, south African forests, northern American chaparral vegetation or African savanna (e.g. Keeley and Bond 1997;Kenny 2000;Gashwa and Michelsen 2002;Thomas et al 2003).…”
Section: Introductionmentioning
confidence: 97%